Memahami Makna : Kaidah ‘Amm dan Khash Serta Amr dan Nahi dalam Ushul Fiqih - A. Adillah Zahiyah Djaka; Adelia Nurinsan; Muhammad Aldi Dahr; Kurniat Kurniat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Rules in Islam such as Amm and Kash as well as Amr and Nahi are used to understand Islamic law. Where these rules are the basis of Ushul fiqih, which discusses the methodology of determining Islamic law. This study uses a literature research method to understand how these rules are used to understand amm and kash as well as amr and nahi in Ushul fiqih. This data is collected from various written sources such as books, journals, literature and scientific publications. The rule of 'amm and kash' is used to understand the verses of the Qur'an and Hadith.